Pemberdayaan ibu dengan edukasi literasi digital sebagai strategi mediasi orangtua dalam mengontrol penggunaan gadget pada anak usia sekolah - Sarini Sarini; Dewi Rubi Fitriyani; Dayana Noprida; Komalasari Komalasari (JOURNAL of Public Health Concerns, 2026)
Background: The rapid advancement of digital technology has made gadgets an integral part of the lives of primary school-aged children. While gadgets offer educational benefits, uncontrolled use can potentially lead to negative impacts on children's physical, psychological, social, and behavioral well-being. Mothers, as primary caregivers, play a crucial role in supervising and mediating their children's gadget usage. Purpose: To enhance mothers' digital literacy regarding the supervision of children's gadget use through an e-module-based parental mediation strategy. Method: The activity was conducted on July 5, 2026, at the Puri Calisya Indah Housing Complex (Block C3, RT 43, Cibalado Hamlet, Gintungkerta, Klari, Karawang). The target audience consisted of mothers with primary school-aged children (6–12 years old), with a total of 25 participants. The primary educational materials used were a digital literacy e-module and leaflets. Pre-test and post-test data were analyzed descriptively by comparing the average scores before and after the intervention. The increase in scores served as an indicator of the community service activity's success in improving participants' knowledge and understanding regarding the supervision of children's gadget use. Results: The findings indicate that prior to the educational activity, 32.0% of respondents fell into the "good" knowledge category, 24.0% into "fair," and 44.0% into "poor." Following the activity, there was a proportional shift, with 80.0% falling into the "good" category, 16.0% into "fair," and 4.0% into "poor." Additionally, the respondents' average knowledge score rose from 74 points at the pre-test stage to 89 points at the post-test stage. Conclusion: Community service activities involving outreach and digital literacy education successfully improved mothers' knowledge regarding the supervision of children's gadget usage. Empowering mothers through digital literacy covering topics such as digital parenting, safe screen time limits, parental mediation strategies, and the use of the Google Family Link app to monitor and restrict gadget usage duration serves as a vital strategy and a positive program for fostering a healthy family environment that supports children's growth and development. Keywords: Community service; Digital literacy; Gadgets; Parental mediation; School-age children Pendahuluan: Perkembangan teknologi digital yang semakin pesat telah menjadikan gadget sebagai bagian dari kehidupan anak usia sekolah dasar. Meskipun gadget dapat memberikan manfaat edukatif, penggunaan yang tidak terkontrol berpotensi menimbulkan dampak negatif terhadap kesehatan fisik, psikologis, sosial, dan perilaku anak. Ibu sebagai pengasuh utama memiliki peran penting dalam melakukan pengawasan dan mediasi penggunaan gadget. Tujuan: Untuk meningkatkan literasi digital ibu melalui strategi mediasi orang tua berbasis e-modul dalam pengawasan penggunaan gadget pada anak. Metode: Kegiatan dilaksanakan pada 5 Juli 2026 di Perum Puri Calisya Indah Blok C3 RT 43 Dukuh Cibalado Gintungkerta Klari Karawang. Sasaran kegiatan adalah ibu rumah tangga yang memiliki anak usia sekolah dasar (6–12 tahun). Jumlah peserta yang berpartisipasi sebanyak 25 orang. Media utama yang digunakan dalam kegiatan ini adalah e-modul edukasi literasi digital dan leaflet. Data hasil pretest dan posttest dianalisis secara deskriptif dengan membandingkan rata-rata skor sebelum dan sesudah intervensi. Peningkatan skor digunakan sebagai indikator keberhasilan kegiatan pengabdian dalam meningkatkan pengetahuan dan pemahaman peserta mengenai pengawasan penggunaan gadget pada anak. Hasil: Menunjukkan bahwa tingkat pengetahuan responden sebelum kegiatan edukasi adalah sebesar 32.0% kategori baik, sebesar 24.0% kategori cukup, dan sebesar 44.0% kategori kurang, sedangkan setelah kegiatan edukasi mengalami peningkatan secara proporsional menjadi sebesar 80.0% kategori baik, sebesar 16.0% kategori cukup, dan sebesar 4.0% kategori kurang. Sedangkan rata-rata skor pengetahuan responden mengalami peningkatan dari 74 poin pada saat pretest menjadi 89 poin pada posttest. Simpulan: Kegiatan pengabdian masyarakat melalui penyuluhan dan edukasi literasi digital berhasil meningkatkan pengetahuan ibu dalam pengawasan penggunaan gadget pada anak. Pemberdayaan ibu melalui literasi digital yang meliputi pola asuh digital, batas aman screen time, strategi mediasi orang tua dan aplikasi google family link untuk mengawasi dan membatasi durasi penggunaan gadget pada anak dapat menjadi strategi penting dan program positif dalam menciptakan lingkungan keluarga yang sehat dan mendukung tumbuh kembang anak.